Gesturing Meaning: Non-action Words Activate the Motor System - Bach, Patric; Griffiths, Debbra; Weigelt, Matthias; Tipper, Steven (Frontiers in Human Neuroscience, 2010)
Across cultures, speakers produce iconic gestures, which add – through the movement of the speakers’ hands – a pictorial dimension to the speakers’ message. These gestures capture not only the motor content but also the visuospatial content of the message. Here, we provide first evidence for a direct link between the representation of perceptual information and the motor system that can account for these observations. Across four experiments, participants’ hand movements captured both shapes that were directly perceived, and shapes that were only implicitly activated by unrelated semantic judgments of object words. These results were obtained even though the objects were not associated with any motor behaviors that would match the gestures the participants had to produce. Moreover, implied shape affected not only gesture selection processes but also their actual execution – as measured by the shape of hand motion through space –, revealing intimate links between implied shape representation and motor output. The results are discussed in terms of ideomotor theories of action and perception, and provide one avenue for explaining the ubiquitous phenomenon of iconic gestures.